Integrated Surveillance and Reservoir Characterization Evaluation for Preliminary Water Injection Optimization Strategy of Carbonate Reservoir - Setiawan, Redy; Buntoro, Aris; Swadesi, Boni; Latuan, Ferdinandus K.; Omar, Shaziera; Murtaza, Ammar S.N. (International Journal of Petroleum Technology, 2024)
The RS field is a green oil field that is in development stage with a carbonate reservoir as the interest zone. A Zone is one of the reservoir zones of the field with the highest oil reserve and has been produced since October 2019. A water injection program has been applied through one injection well since November 2020. The significant pressure decline is an indicator that the injection program in A Zone is not optimum in maintaining the reservoir pressure. There is no dynamic model for reservoir performance forecasting. Therefore, a further detail and comprehensive analysis through monitoring surveillance and reservoir characterization is required. The objective is to optimize the pressure maintenance program and to increase the oil recovery of A Zone in RS field. This study consists of three steps of analysis: the evaluation of existing water injection (pressure maintenance) surveillance; reservoir characterization evaluation; and 1-D reservoir simulation study. Surveillance analysis includes production and injection performance analysis; pressure performance analysis; voidage replacement ratio (VRR) analysis; Hall’s Plot analysis and Chan’s Diagnostic Plot analysis. Reservoir characterization evaluation includes remaining reserve evaluation; drive mechanism analysis; reservoir displacement profile phase based on fractional flow analysis (Buckley-Leverett); quality and reservoir heterogeneity; and reservoir pressure condition analysis. Material balance modelling is used as an initial simulation for optimization of injection wells and production performance prediction. Based on production prediction model material balance, if produced with VRR = 1, until the end of the contract (October 2039), the A Zone reservoir is capable of producing oil with a flow rate of 3038.36 BOPD; capable of maintaining reservoir pressure up to 1679.28 psig; water cut reservoir reached 77.82%; and cumulative oil production is 31.14MMSTB or equivalent to 12.50% of recovery factor.